2010
DOI: 10.4028/www.scientific.net/msf.650.126
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy Phonon Scattering and Thermoelectric Properties in In<sub>2</sub>Te<sub>3</sub>–SnTe Compounds

Abstract: Solid solution formation is a common and effective way to reduce the lattice thermal conductivity for thermoelectric materials because of additional phonon scattering by point defects and grain boundaries. In the present work we prepared In2Te3–SnTe compounds using a mild solidification technique and evaluated their thermoelectric properties in the temperature range from 318705 K. Measurements reveal that the transport properties are strongly dependent on the chemical composition  In2Te3 content, and lattice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…The highest a value of (In 1.9 Al 0.1 Te 3 ) 0.08 (SnTe) 0.92 is 83 lV K À1 at 668 K, only slightly higher than that of the Al-free (In 2 Te 3 ) 0.08 (SnTe) 0.92 sample. 3 Jovovic et al 13 suggested that such an unchanged a value results from indium impurity levels that pin the Fermi level. Figure 4 shows the electrical conductivity (r) as a function of temperature for the two samples; the r value gradually decreases with increasing temperature.…”
Section: Te Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…The highest a value of (In 1.9 Al 0.1 Te 3 ) 0.08 (SnTe) 0.92 is 83 lV K À1 at 668 K, only slightly higher than that of the Al-free (In 2 Te 3 ) 0.08 (SnTe) 0.92 sample. 3 Jovovic et al 13 suggested that such an unchanged a value results from indium impurity levels that pin the Fermi level. Figure 4 shows the electrical conductivity (r) as a function of temperature for the two samples; the r value gradually decreases with increasing temperature.…”
Section: Te Propertiesmentioning
confidence: 98%
“…2 Recent work in our group revealed that In-Sn-Te-based alloys have low electrical and thermal conductivity. 3 This low electrical conductivity might be caused by low carrier concentration and high carrier scattering. From the microstructural point of view, it seems easier to improve the electrical conductivity of this material rather than the Seebeck coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, In has also been frequently considered as a doping element in Sb 2 Te 3 , which may lead to intrinsic vacancies with the high density at cation sites owing to the lattice mismatch between indium (In 3+ ) (In 3+ is supposed to substitute Sb 3+ ) and tellurium ions (Te 2− ) [25,26]. Therefore, TE performance should be enhanced via phonon-vacancy scattering, which plays a substantial role in reducing thermal conductivity [27][28][29]. In summary, In is a promising doping element for improving the TE properties of the Sb 2 Te 3 thin film.…”
Section: Introductionmentioning
confidence: 99%